The Model of Union Agriculture in the Perspective of Shari’a Economy to Improve the Prosperity of the Working Farmers - Sutarman, Akmal; Wahid Haddade, Abdul; Hasbiullah (LAA MAISYIR: Jurnal Ekonomi Islam, 2024)
The issue of agricultural profit sharing is still on going and commonly found in Enrekang who have been adopting the model in Union Farming (mangjampang lessuna). This research aims at finding the union farming practice in the subdisctrict of Anggeraja through the perspective of Islamic economy. The method used is the Phenomenology with qualitative approach. The data is taken from both the working farmers and the farm owners. The result of the research indicates that the disparity in profit sharing found within the union farming practices has generated issues and deemed unfair by the farmers. Among the factors that caused the difference in this system are the funders or investors, farmers themselves, non- binding agreement and humanitarian considerations. Through the viewpoint of shari’a economy the practice of union farming has not fulfilled the pact of Muzara’ah and therefore another model called Mangjampang Lassuna Syariah (MLS) is proposed as fair profit sharing farming concept. A good faming practice should not only aim at making profits but also ensuring prosperity and fairness for both parties.